Obesity, diabetes and COVID-19: morbidity and mortality in a private hospital in western Paraná (Research, Society and Development, 2023)
Objective: to quantitatively and qualitatively analyze patients hospitalized for COVID-19 at Hospital São Lucas, in the city of Cascavel - PR, correlating the prognosis of these patients with preexisting morbidities such as obesity and diabetes mellitus. Methods: This was a cross-sectional, retrospective, quantitative and qualitative exploratory research that collected data from January to June 2021. Data from medical records of 385 patients, admitted by COVID-19 and seen at Hospital São Lucas, were used. Results: in the 385 patients analyzed, 66% were male and 87.4% were older than 41 years. Diabetics were 16.9% of the sample. BMI indicated overweight or obesity in 74.9%. Most remained hospitalized from 4 to 14 days. About the radiological analysis, 91.3% had pulmonary involvement, which was from 26% to 75% of the parenchyma in 80.61%. Respiratory assistance was required by 94% - in the form of non-invasive mechanical ventilation for 56.9%, and invasive for 37.1. The mortality rate was 27.5% - age, male gender and demand for invasive mechanical ventilation being the most evident risk factors. Conclusion: Age, male gender and need for invasive mechanical ventilation were the worst prognostic factors for COVID-19. Diabetes mellitus was associated with greater lung impairment. BMI was not relevant in the analysis of outcomes, possibly due to the large number of overweight or obese patients in the sample.